2021
DOI: 10.5098/hmt.16.4
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review of Performance Analysis of With and Without Fins Solar Thermal Collector

Abstract: Solar thermal collector is a simple, economic, and environment friendly equipment which is used to utilize solar energy for various agriculture and industrial applications. The investigators mainly focus on the improvement of the thermal performance by providing various fins shapes underside of the absorber plate in the single pass and double pass solar thermal collector. This work discusses the influence of different shaped fins used by various researchers in improving the thermal performance of thermal colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The impacting air jets solar air heater enclosed by fins in the bottom of the absorber region for noncross flow design has been the subject of an experimental investigation for various configurations [6]. According to a review of the literature and comparison research, solar air thermal collectors with fins transmit heat more quickly than those without fins [7]. N. F. Hussein investigated the thermal efficiency of two counterflow double-pass solar air heater configurations: conventional flat plate absorbers and waterfilled tubular capsules.…”
Section: Introductionmentioning
confidence: 99%
“…The impacting air jets solar air heater enclosed by fins in the bottom of the absorber region for noncross flow design has been the subject of an experimental investigation for various configurations [6]. According to a review of the literature and comparison research, solar air thermal collectors with fins transmit heat more quickly than those without fins [7]. N. F. Hussein investigated the thermal efficiency of two counterflow double-pass solar air heater configurations: conventional flat plate absorbers and waterfilled tubular capsules.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the temperature of the thermal output of the parabolic collector at the absorber tube wall increases with rising heat flux, and, it is increased from 350 to 390 K in laminar flow and from 310 to 325 K in a turbulent flow. Kumar et al (2021) presented a comprehensive review of performance analysis of with and without fins SAH. The authors found that the thermal efficiency increases continuously with an increase in fluid mass flow rate, whereas thermohydraulic efficiency increases up to an inception value of fluid mass flow rate, attains a maximum, and then decreases sharply for a given fin spacing and fin height.…”
Section: Introductionmentioning
confidence: 99%
“…The equilateral triangular tube offers the optimum heat storage and release properties, according to the results. (Kumar et al, 2021) By including different fin shapes on the bottom of the absorber plate in single-pass and double-pass solar thermal collectors, it was shown how to increase thermal performance. the impact of various fin shapes employed by researchers to increase the thermal efficiency of thermal collectors.…”
Section: Introductionmentioning
confidence: 99%